2018
DOI: 10.2741/4591
|View full text |Cite
|
Sign up to set email alerts
|

Use of non-ionizing electromagnetic fields for the treatment of cancer

Abstract: Cancer treatment and treatment options are quite limited in circumstances such as when the tumor is inoperable, in brain cancers when the drugs cannot penetrate the blood-brain-barrier, or when there is no tumor-specific target for generation of effective therapeutic antibodies. Despite the fact that electromagnetic fields (EMF) in medicine have been used for therapeutic or diagnostic purposes, the use of non-ionizing EMF for cancer treatment is a new emerging concept. Here we summarize the history of EMF from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…During the final 2 h, cells from both groups (Mag and Sham) were treated with 11.0 mM of [U-13C]glucose (Millipore Sigma, Miamisburg, OH) in DMEM (supplemented with 10% FBS, 2.0 mM glutamine). After 2 hours of magnetic or sham stimulation, the medium was removed by aspiration, cells were washed with cold PBS buffer, trypsinized, cell pellets were snapfrozen in liquid nitrogen, and were stored at -80°C until further analysis by 1 For 1 H-decoupled 13 C NMR experiments, a power-gated sequence with a WALTZ-16 composite pulse (flip-angle = 30°) was used. A 90°pulse with a duration of 10 µs was used with 10,000 scans.…”
Section: Observation Of Caspase3/7 Activation In Gbmmentioning
confidence: 99%
See 1 more Smart Citation
“…During the final 2 h, cells from both groups (Mag and Sham) were treated with 11.0 mM of [U-13C]glucose (Millipore Sigma, Miamisburg, OH) in DMEM (supplemented with 10% FBS, 2.0 mM glutamine). After 2 hours of magnetic or sham stimulation, the medium was removed by aspiration, cells were washed with cold PBS buffer, trypsinized, cell pellets were snapfrozen in liquid nitrogen, and were stored at -80°C until further analysis by 1 For 1 H-decoupled 13 C NMR experiments, a power-gated sequence with a WALTZ-16 composite pulse (flip-angle = 30°) was used. A 90°pulse with a duration of 10 µs was used with 10,000 scans.…”
Section: Observation Of Caspase3/7 Activation In Gbmmentioning
confidence: 99%
“…Electromagnetic fields (EMF) are known to produce anticancer effects in vitro and in vivo ( 1 ). We have shown recently that spinning oscillating magnetic fields (sOMF) produced by rotating permanent magnets in a noninvasive magnetic stimulation device (Oncomagnetic Device), developed by us, rapidly kill patient derived glioblastoma (GBM) and non-small cell lung cancer cells in culture ( 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…This is the case of, e.g., untreatable brain tumors, because certain high-molecular weight and/or hydrophilic anti-cancer drugs cannot penetrate the blood–brain barrier or if all other therapeutic options (radiotherapy, chemotherapy, targeted antibodies, or other pharmacological treatments) cannot eliminate the malignant growth. There are different concepts45 (discussed in more detail below) using different frequencies of the EMF spectrum with or without signal modulation, to treat specific tumors, with electric (TTFields, electroporation) or EMFs (hyperthermia, RF treatment), or in combination with chemotherapeutics or nanoparticles (see also Table 2).…”
Section: Cancer Treatmentmentioning
confidence: 99%
“…Recently the WHO’s International Agency for Research on Cancer listed radio‐frequency electromagnetic fields (RF‐EMFs), ranging from 10 MHz to 300 GHz, as potentially carcinogenic (Baan et al, 2011). On the other hand, an increasing number of studies reported EMFs beneficial role in the treatment of numerous chronic diseases, such as cancer, mood disorders and many forms of neurodegeneration (Jimenez et al, 2018; Martiny et al, 2010; Wyszkowska et al, 2019), paving the way for the therapeutic use of magnetic‐field based techniques, such as Transcranial Magnetic Stimulation and Pulsed Electromagnetic Field (PEMF) stimulation (Hallett, 2000; Markov, 2007).…”
Section: Introductionmentioning
confidence: 99%